The Logic Probability On Hadith (Counting Gender Occupants Of Heaven And Hell) - Ruhama Wazna; Hamim Ilyas (Jurnal Ushuluddin, 2019)
This study aims to explore probability as one of the new methods of understanding the hadith about the majority of women who inhabit hell by integrating the ratio of male and female hadith at the end of time as the counting scale. The use of the thematic-multidimensionality method, this study construed and elaborated the related hadith (al-jam'u bain al-adillah). The results of the study revealed that the more women than men in the world, affecting the majority of women as residents of heaven and hell, and vice versa, affecting the minority of men as residents of heaven and hell. It proves the misogyny assumed in the hadith was not essential. Thus, it is not appropriate if this hadith used as a tool to discredit women have a bad character so that they become the most occupants of hell than men, or conversely reject the hadith that is authentic only because of reasons contrary to reason